Defisit Evapotranspirasi sebagai Indikator Kekurangan Air pada Padi Gogo (Oryza sativa L.) - Sulistyono, Eko; Suwarto, ,; Ramdiani, Yulianti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
The research was conducted to study the correlation between deficit of evapotranspiration and yield decreasing. Factorial experiment was arranged in Randomized Block Design. First factor was irrigation frequency of 1, 2, 4 and 6 days. Second factor were nine upland rice lines. Evapotranspiration was measured with simple lysimeter based on water balance. There was positive correlation between deficit of evapotranspiration and yield decreasing. Defisit of evapotranspiration as much as 240.06 mm caused yield decreasing of 90% and dry matter weight decreasing of 72.5%. The relation between total evapotranspiration (E, mm) and dry matter weight (DM, g/plant) was DM = 0.0245 E + 13.85. Water use efficiency or yield and evapotranspiration ratio correlated with leaf width and sum of seed each panicle positively . Increasing leaf width and sum of seed each panicle could increase water use efficiency. Key Words : evapotranspiration, water use efficiency, upland rice, lysimeter.